Complex therapy for patients with respiratory infections and respiratory diseases - I. V. Kovaleva; N. D. Fomenko (Лечащий Врач, 2021)
The article provides an overview of the symposium on the complex therapy of patients with respiratory infections and diseases of the respiratory tract, held on October 29, 2020 with the support of Materia Medica Holding as part of the XXX National Congress on Respiratory Diseases, which was held from October 27 to 30 online with the support of the Russian Respiratory Society and the Ministry of Health of the Russian Federation. The aim of the symposium was to familiarize physicians, general practitioners, pulmonologists and infectious disease specialists with possible ways of managing patients with respiratory diseases caused by respiratory infections, as well as with the results of randomized clinical trials (RCTs) on the management of patients with chronic obstructive pulmonary disease (COPD). The co-chairs of the symposium and keynote speakers were three leading experts in this field – professors A. A. Zaitsev (Moscow), R. F. Khamitov (Kazan) and A. A. Wiesel (Kazan). At the symposium, the results of RCTs were presented, proving the effectiveness of antiviral and immune stimulating drug in influenza and other acute respiratory viral infections, regardless of the timing of the therapy started, its favorable safety profile, as well as the ability to reduce the need for antipyretic drugs and help prevent bacterial complications. Data from another RCT demonstrate the ability of antitussive drug to reduce cough and reduce its severity in COPD, reducing the impact of COPD on patients' lives.